Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1016/j.dib.2019.103868
|View full text |Cite
|
Sign up to set email alerts
|

Compendium of hand, foot and mouth disease data in Malaysia from years 2010–2017

Abstract: This data article is constructed using information from hand, foot and mouth disease outbreaks in every Malaysian state. Important information like total number of cases from every state and age group, humidity, air temperature and wind as well as types of viruses isolated from patients infected with hand, foot and mouth disease were gathered and sorted into four tables. The information sources include Malaysian Administrative Modernisation and Management Planning Unit (MAMPU), National Centre for Biotechnolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 12 publications
(12 reference statements)
0
5
0
Order By: Relevance
“…2,3 Therefore, this disease poses a serious threat to public health in countries with a high incidence, such as China and other Asia-Pacific countries. [4][5][6][7][8] China accounted for 86% of the total cases reported to the WHO between 2010 and 2014, and it reported an alarming number of approximately 2.7 million cases of HFMD, resulting in 384 deaths in 2014. 9 Although vaccines against EV-71 for children aged 6 months to 5 years have been available since 2015, no effective vaccines for other Coxsackieviruses exist yet, and the incidence of HFMD has not decreased.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Therefore, this disease poses a serious threat to public health in countries with a high incidence, such as China and other Asia-Pacific countries. [4][5][6][7][8] China accounted for 86% of the total cases reported to the WHO between 2010 and 2014, and it reported an alarming number of approximately 2.7 million cases of HFMD, resulting in 384 deaths in 2014. 9 Although vaccines against EV-71 for children aged 6 months to 5 years have been available since 2015, no effective vaccines for other Coxsackieviruses exist yet, and the incidence of HFMD has not decreased.…”
Section: Introductionmentioning
confidence: 99%
“…The inclusion and exclusion procedure followed protocols of John et al. (2018a , b) and Nelson et al., 2019a , Nelson et al., 2019b where keywords from the primary associations are used independently or added together (in combination of two or more) with activities, aspects and region ( Table 1 ). These keywords revealed several documents in Scopus (n = 64), Web of Science (n = 71), Google Scholar (n = 103) and National Centre for Biotechnology Information (n = 1262).…”
Section: Methodsmentioning
confidence: 99%
“…In a few studies, it has been reported that close contacts are at risk of developing the disease since the virus is shed from the stools of the infected person for many weeks. 5…”
Section: Etiology and Epidemiology Hfmdmentioning
confidence: 99%